Law Enforcement Against Cybercrime in Online Activities - Novi Hermawati; Faisal Santiago (Publikasiku, 2023)
The development of information and communication technology makes the relationship between individuals and groups with the world not limited to existing norms so that it can cause a change in all fields. The changes also have a major impact on the transformation of values in society. It occurs not only positive but also negative consequences. Information and communication technology used for crime is known as cybercrime. Cybercrime has been confirmed to be adverse to the worldwide community, at the same time as efforts to get rid of cybercrime are nevertheless hampered through numerous factors, therefore, a crook regulation coverage is wanted towards cybercrime crimes. This paper discusses two problems, namely, first, how to enforce the law against cybercrime in the legislation in Indonesia, and second, how the strategy for eradicating cybercrime is formulated in the Law on Information and Electronic Transactions. Law enforcement against cybercrime is performed through criminal and non-criminal policies. Meanwhile, to eradicate cybercrime, it is necessary to prepare appropriate laws and provide legal provisions for law enforcement officers.